2016
DOI: 10.2147/dddt.s123412
|View full text |Cite
|
Sign up to set email alerts
|

Development of a chitosan based double layer-coated tablet as a platform for colon-specific drug delivery

Abstract: A double layer-coated colon-specific drug delivery system (DL-CDDS) was developed, which consisted of chitosan (CTN) based polymeric subcoating of the core tablet containing citric acid for microclimate acidification, followed by an enteric coating. The polymeric composition ratio of Eudragit E100 and ethyl cellulose and amount of subcoating were optimized using a two-level factorial design method. Drug-release characteristics in terms of dissolution efficiency and controlled-release duration were evaluated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…A normal distribution is considered a crucial assumption for statistical analysis. Normal probability plots for standardized residuals were linear, indicating that the experimental run data were normally distributed ( Supplementary Figure S1A ).4, 43 4 Pareto charts indicating the relative importance of the individual and interaction effects based on Student’s t -tests are shown in Supplementary Figure S1B . Statistically significant independent factors were extended the dotted bar which positioned at α = 0.05.…”
Section: Resultsmentioning
confidence: 99%
“…A normal distribution is considered a crucial assumption for statistical analysis. Normal probability plots for standardized residuals were linear, indicating that the experimental run data were normally distributed ( Supplementary Figure S1A ).4, 43 4 Pareto charts indicating the relative importance of the individual and interaction effects based on Student’s t -tests are shown in Supplementary Figure S1B . Statistically significant independent factors were extended the dotted bar which positioned at α = 0.05.…”
Section: Resultsmentioning
confidence: 99%
“…However, the amount of β-carotene in the intestinal phase (bioaccessibility) increased significantly, which is in agreement with the expected behaviour for these polymers that swell at neutral pHs. Kim et al [ 54 ] reported that ethylcellulose coatings are able to retard the gastric and intestinal drug release, which is then gradually released in the colon. Drug release was impeded by the layer of ethylcellulose, regardless the acidity of the medium.…”
Section: Resultsmentioning
confidence: 99%
“…A double-layer coated colon-specific drug delivery system was developed by Kim et al The system consisted of a chitosan-based polymeric subcoating of the core tablet (containing citric acid for microclimate acidification), followed by an enteric EC coating. The system showed drug release in a controlled manner by inhibiting drug release in the stomach and intestine, but releasing the drug gradually in the colon [32]. The example of utilizing EC as a release-retarding coating is a commercially available preparation called Micro-K ® in hard gelatin capsules, containing small crystalline particles of potassium chloride (KCl).…”
Section: Applicability Of Ec In Pharmaceutical Formulationsmentioning
confidence: 99%